As the devil dares - Harrington, Anna (Romance fiction writer) (Harrington, Anna (Romance fiction writer) Capturing the Carlisles novel., 2018)
Whether it's business or pleasure, Lord Robert Carlisle never backs down from a dare. But finding a husband for scandalous Mariah Winslow? It's one challenge he instantly regrets accepting. Even with all his connections---and rakish charms---Robert will have to use every trick in the book to marry off a woman with no dowry and no sense of decorum...no matter how stunningly beautiful she is. Mariah Winslow has no intention of being a pawn in Lord Robert's game. She knows he agreed to play matchmaker only to secure a partnership in her father's shipping company, a partnership that's rightfully hers. For now, though, she'll dress for the elegant balls he throws and dance with the eligible bachelors he chooses. But she won't be outwitted by the devil himself---no matter how tempting and irresistible she finds him.